Effect of Green Economy Variable on Sumatera Regional Income (2018-2023) - Wahyu Nur Inayati; Ratu Eva Febriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Increasingly rapid economic growth has not only met human material needs, but also increased global environmental pollution which requires every country to pay a heavy price for climate change and environmental pollution that occurs. The environmental problems that occur urge policies to implement a green economy as a solution to the most urgent and effective environmental problems. This research was conducted by analyzing the issue of implementing a green economy on regional income growth. This research aims to see the influence of factors in implementing the green economy concept on the economic growth of the Sumatra region. The analytical method used is quantitative analysis with a panel data regression model consisting of common effect, fixed effect and random effect approaches from secondary data on green economy variables, namely public data on air quality index as an environmental pillar, life expectancy, average length of schooling. , and the open unemployment rate as a social pillar, fiscal spending based on its function as an economic pillar and the GRDP level at constant prices in 10 Sumatra Provinces from 2018-2023. This research shows that there is a positive and significant influence between the green economy on regional income, namely life expectancy and average length of schooling, while the environmental quality index, open unemployment rate and fiscal spending have a negative and insignificant effect on regional income.